American Catholic : The Politics of Faith During the Cold War - Hart, D. G. (Darryl G.) (Book collections on Project MUSE., 2020)
"American Catholic places the rise of political conservatism, typically associated with William F. Buckley, Jr., Barry Goldwater, and Ronald Reagan, in the context of ferment within the Roman Catholic Church"--